Analisis Pengaruh Eko Efisiensi, Inovasi Hijau, Pengungkapan Emisi Karbon, Dan Kinerja Lingkungan Terhadap Nilai Perusahaan Dengan Ukuran Perusahaan Sebagai Variabel Kontrol - Santoso, Al’ainaa Meuthia Maulida; Yanti , Harti Budi (CV. ITTC INDONESIA, 2024)
This research aims to analyze the influence of eco-efficiency, green innovation, carbon emission disclosure, and environmental performance on corporate value. The research sample consists of Consumer Non-Cyclical companies listed on the Indonesia Stock Exchange during the 2021-2023 period and received the PROPER ratings through the KLHK website. The research results show that eco-efficiency, green innovation, carbon emission disclosure, and environmental performance has a positive effect on corporate value.